TNF-α Levels in Respiratory Samples Are Associated with SARSCoV- 2 Infection - Pereson Moschen, Matias Javier (2022)
The aim of this study was to evaluate concentrations of IL-6 and TNF-α in swab samples from individuals with symptoms compatible with COVID-19 and analyze their association with SARS-CoV-2 genome presence.The study was conducted on 127 combined nasopharyngeal and oropharyngeal swabs, referred to the laboratory for detection of SARS-CoV-2. Cytokine levels of symptomatic individuals with detectable (n = 52) or undetectable (n = 33) SARS-CoV-2 were measured. A group consisting of asymptomatic individuals and negative for SARS-CoV-2 genome (n = 42) were included to obtain cytokines? normal range. Concentrations of TNF-α (standard curve range: 0 to 500 pg/mL) and IL-6 (standard curve range: 0 to 300 pg/mL) in swabs were determined using commercial reagents based on enzyme linked immunosorbent assay (BD-Biosciences).TNF-α levels were higher in SARS-CoV-2 (+) symptomatic group (mean: 16 pg/mL, median value: 5.88 (5 to 172.1) pg/mL) compared with SARS-CoV-2 (?) symptomatic individuals (mean: 7.6 pg/mL, median: 5.00 (5 to 69.9) pg/mL) (P = 0.0009) (Fig. 1Bi). IL-6 was increased in some individuals with no significant difference between groups (mean: 33.95 pg/mL, median: 5.40 (5 to 467) pg/mL and for SARS-CoV-2 (?) mean: 30.4 pg/mL, median: 6.07 (5 to 466.6) pg/mL) (Fig. 1Bii). Considering a threshold value of 10 pg/mL for TNF-α, individuals with SARS-CoV-2 (+) were six times more likely to display increased levels of TNF-α (OR = 5.7; P = 0.006; 95% CI = 1,551 to 19,11). A correlation between TNF-α or IL-6 levels and viral load (Ct) was not found. Furthermore, age and gender were not related with cytokine concentration among SARS-CoV-2 (+) group. Focusing only on hospitalized patients, individuals with viral genome presence showed increased TNF-α values (mean: 18.7 pg/mL, median 5 pg/mL; 5 to 172.2) compared with those with absent SARS-CoV-2 genome (mean: 7.95 pg/mL, median 5 [5 to 65] pg/mL) (P = 0.028).Our findings, evaluating the concentration of TNF and IL-6 at the entry site of SARS-CoV-2, highlight the pleiotropic role of IL-6 in local inflammation process and show that TNF-α could contribute to disease evolution prognosis as a biomarker. Measurement of TNF-α in nasopharyngeal swabs at diagnosis could identify those individuals that may benefit from immunomodulatory and cytokine inhibiting therapies.